Core-shell structured nanoprecipitates in zirconium based alloy. (August 2020) - Liu, Chengze; Li, Geping; Yuan, Fusen; Han, Fuzhou; Ali, Muhammad; Zhang, Yingdong; Guo, Wenbin; Gu, Hengfei
Abstract: Unique precipitations with core-shell structure between metal and intermetallics were firstly observed in zirconium based alloy. The spherical core structure was identified as tetragonal Zr3 Ge nanoprecipitate, and the shell structure was determined to be face-centered-cubic (FCC) zirconium phase, which uniformly encircled the Zr3 Ge nanoparticle while obeying the orientation relationship with the hexagonal-close-packed (HCP) zirconium phase matrix: [ 1 1 0 ] FCC / / [ 2 1 ¯ 1 ¯ 0 ] HCP and ( 1 1 ¯ 1 ) FCC / / ( 0001 ) HCP . Based on electron microscopy characterization and theoretical analysis, the formation mechanism of the core-shell structured nanoprecipitates was proposed. Graphic abstract: Image, graphical abstract